Vocabularies for describing datasets on the Web - Pastor-Sánchez, Juan-Antonio (Anuario ThinkEPI, 2017)
The technologies of the semantic web have reached a high degree of development. There are hundreds of metadata schemes and ontologies and thousands of datasets available for public use. The next step is to improve access, reuse and trust on datasets. This article includes vocabularies for describing datasets (DCAT) and their provenance (PROV-O), specifying mechanisms for access and use of data (DUV), and defining quality indicators (DQV).
Keywords: Metadata; Vocabularies; Ontologies; Semantic web; Datasets; DCAT; PROV-O; DUV; DQV.